2014
DOI: 10.1631/jzus.b1300229
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization?

Abstract: Abstract:Objective: To explore whether there exist differences in cognitive development between singletons and twins born after in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Methods: A total of 566 children were recruited for the study, including 388 children (singletons, n=175; twins, n=213) born after IVF and 178 children (singletons, n=87; twins, n=91) born after ICSI. The cognitive development was assessed using the Chinese-Wechsler Intelligence Scale for Children (C-WISC). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…At the first exploration, the contralateral implanted embryo was too underdeveloped to be spotted by laparoscopy, which contributed to the consequently delayed diagnosis of ectopic pregnancy. IVF or intracytoplasmic sperm injection (ICSI) following ovulation induction has shown adverse effect on offspring, and this study showed the association of ovulation with bilateral ectopic pregnancy (Wang et al, 2013;Xing et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…At the first exploration, the contralateral implanted embryo was too underdeveloped to be spotted by laparoscopy, which contributed to the consequently delayed diagnosis of ectopic pregnancy. IVF or intracytoplasmic sperm injection (ICSI) following ovulation induction has shown adverse effect on offspring, and this study showed the association of ovulation with bilateral ectopic pregnancy (Wang et al, 2013;Xing et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, the remaining 19 studies found no significant differences in neurodevelopment between ICSI‐ and IVF‐conceived children (Bonduelle et al ., , , ; Van Golde et al ., ; Leslie et al ., ; Place & Englert, ; Squires et al ., ; Barnes et al ., ; Papaligoura et al ., ; Ponjaert‐Kristoffersen et al ., ; Sutcliffe et al ., ; Wennerholm et al ., ; Knoester et al ., , ; Palermo et al ., ; Xing et al ., , ; Schendelaar et al ., ; Punamäki et al ., ). A few also stratified male infertility by individual semen parameters, and found no association between presence or nature of paternal sperm abnormalities and delayed development (Bonduelle et al ., ; Leslie et al ., ; Wennerholm et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Knoester et al . (,b) also documented a lower IQ in similarly aged ICSI‐ compared to IVF‐conceived infants, but this finding did not reach statistical significance, and larger studies have demonstrated no differences using a wider range of cognitive measures (Leslie et al ., ; Place & Englert, ; Ponjaert‐Kristoffersen et al ., ; Xing et al ., ). The sample size was also too small to draw firm conclusions on differences in problem behaviors between ICSI‐ and IVF‐conceived girls, as reported in another study by Knoester et al .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, different selection criteria were applied, thus yielding variable results. For instance, children born after ovulation induction have been included in the analysis of cohorts of children conceived via ART; in addition, both preterm and full-term children were included in the same analyses (Ito et al, 2006;Xing et al, 2014;Ramoğlu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term functional problems are often reported for full-term children conceived via IVF in comparison with their naturally conceived peers (Bay et al, 2013;Bay, 2014). However, the published data concerning developmental outcomes in preterm children conceived via IVF are sparse (Ito et al, 2006;Xing et al, 2014;Ramoğlu et al, 2016); to date, there has been no study evaluating the educational and other long-term outcomes at school age, a highly challenging developmental stage, in very preterm children born after assisted reproduction, including IVF. The aim of this study was to compare the school performance and longterm outcomes of very preterm children conceived via IVF versus their naturally conceived peers.…”
Section: Introductionmentioning
confidence: 99%